Hassan Ibn Thabit’s poetry - Hasan, Md. Mahmudul (2020)
While in a Muslim educational setting the study of most western writers may trigger a “fragmented existence” among the learners, that of a poet like Hassan ibn Thabit will give them a strong sense of belonging. It is important to discuss the poet among Muslims not only because of his religion or because of his status as the “Poet of the Prophet,” but also because of his creative genius. He was a legendary literary figure even before Prophet Muhammad migrated from Makkah to Madinah, as he had connections with the Ghassanid and Lakhmid rulers. He is widely known as a mukhadram or the owners of two lives, because he lived sixty years before embracing Islam and another sixty years afterwards. In both periods, he composed astounding amount of poetry. After embracing Islam, he changed the trajectory of the subject matter of his poetry and played a key role in defending Islam and the character of Prophet Muhammad from the slanders of the non-believing poets.